Identifying Critical Success Factors of Lean Six Sigma and Performance Measurement using Balanced Scorecard Perspective - Md fauzi Ahmad; Shafeeka Fadlikh Zamri; Arman Shah Abdullah; Nor aida Abdul Rahman; Eko Wahjudi; Mohd Nasrun Mohd Nawi (International Journal of Supply Chain Management, 2020)
Lean Six Sigma (LSS) became one of the most important and established business process enhancement technique to improve organisation performance. There are many tools and techniques for quality improvement. However, most of previous tools and techniques are focusing on continuous improvement in general. LSS is more specific focusing on how to improve waste and improving variance in the process drastically, finally improving financial and profit to the company. In addition, there are less study of LSS towards Balanced Scorecard (BSC). The aim of this paper is to review published literature on Lean Six Sigma (LSS) critical success factors (CSFs) and Balanced Scorecard (BSC) perspective in manufacturing industries. The methodology included reviewing literature from well-known databases such as Science Direct, Scopus, Emerald and also Google Scholar. This paper content results of past literature on the CSFs of LSS and BSC’s performance measurement. The finding shows that five CSFs achieved highest frequency are; (i) training and education, (ii) top management involvement and commitment, (iii) organizational infrastructure, (iv) linking LSS to business strategy and (v) cultural change. For balance scorecard, financial, customer, internal business processes and learning and growth are the highest frequency.